Winter Feed Estimator: A Practical Tool for the Beef Cow-Calf Producer - Mark Warren; Ed Jennings; Matt Hersom (EDIS)
AN244, a 3-page fact sheet by Mark Warren, Ed Jennings, and Matt Hersom, provides a simple approach for estimating dry matter feed requirements of the beef herd and then converting those requirements into an estimate of required hay or silage round rolls. Published by the UF Department of Animal Science, June 2010.